Strong spin-orbit torque effect on magnetic defects due to topological surface state electrons in Bi2Te3 - Kosma, Adamantia; Ruessmann, Philipp; Blügel, Stefan; Mavropoulos, Phivos (PHYSICAL REVIEW B, 2020)
We investigate the spin-orbit torque exerted on the magnetic moments of the transition-metal impurities Cr, Mn, Fe, and Co, embedded in the surface of the topological insulator Bi2Te3, in response to an electric field and a consequent electrical current flow in the surface. The multiple scattering problem of electrons off impurity atoms is solved by first-principles calculations within the full-potential relativistic Korringa-Kohn-Rostoker (KKR) Green function method, while the spin-orbit torque calculations are carried out by combining the KKR method with the semiclassical Boltzmann transport equation. We analyze the correlation of the spin-orbit torque to the spin accumulation and spin flux in the impurities and unveil the effect of resonant scattering. In addition, we relate the torque to the resistivity and Joule heat production. We predict that the Mn/Bi2Te3 is optimal among the studied systems.